(untitled) (Al-Farooq Journal of Sciences, 2026)
This research presents an analytical study of the most significant ideas advanced by the French philosopher Jean-Paul Sartre concerning the philosophy of commitment (engagement). The study demonstrates that Sartre adopted, through his literary works, the role of the committed writer, emphasising the writer’s moral responsibility within society. Consequently, literature assumed a prominent role in transforming and advancing social reality. Sartre’s conception of commitment is distinctive in that he argued that only the writer is obliged to adhere to the principle of commitment, while excluding poets, painters, and other artists from this obligation. Furthermore, Sartre maintained that individual freedom does not necessarily imply separation from society; rather, true freedom is realised through conscious interaction with others and through an individual’s commitment to the issues and concerns of society. Sartre also regarded his own literature as literature of commitment to a particular stance, one that is both ethical and social in response to events. His approach combined both individual and social dimensions, placing ethical and social values at the forefront of literature, while artistic and imaginative values occupied a secondary position.